Defining glaucomatous optic neuropathy using objective criteria from structural and functional testing. Issue 6 (22nd July 2020) - Iyer, Jayant Venkatramani; Boland, Michael V; Jefferys, Joan; Quigley, Harry
Abstract : Background/Aims: To identify objective criteria from optical coherence tomography (OCT) and perimetry that denote a useful, specific definition of glaucomatous optic neuropathy (GON) in eyes with open-angle glaucoma for comparisons among glaucoma research studies. Methods: A cross-sectional study of adult patients with glaucoma from nine centres on five continents evaluated de-identified physician diagnosis, OCT and perimetry results for 2580 eyes (1531 patients) in an online database. Each eye was graded by their glaucoma specialist as either definite, probable or not GON. Objective measures from OCT and perimetry, derived from an online consensus panel comprising 176 glaucoma specialists globally, were compared against the three diagnostic levels. Results: Diagnoses were 54% 'definite', 22% 'probable' and 24% 'not GON'. Using only OCT data or only field data had inadequate specificity (<90%). The best definitional choice for data from either the most recent or the preceding OCT/field pair had 77% sensitivity at 98% specificity and consisted of abnormal OCT superior or inferior nerve fibre layer quadrant with matching, opposite, abnormal Glaucoma Hemifield Test. Conclusions: Objective criteria to define GON are practical and may be useful for comparisons among clinical studies to supplement subjective clinical assessment.